Case report: Acute Kidney Injury, Liver impairment, Severe Anemia in a child with Malaria and Hyperparasitaemia - Harshil Gumasana; Walter Otieno (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Severe Malaria is a medical emergency mainly because of its rapid progression to complications and death if not promptly and adequately treated. In 2018 WHO put the incidence of P. falciparum Malaria in the African region to be around 99.7%. We present a case where a boy who presented with high grade fever, prostration, and jaundice. On investigation he was found to have parasitemia of 35%, met multiple criteria for Severe Malaria namely: Hyper-parasitemia, Thrombocytopenia, Anemia and Metabolic acidosis. The child was treated with I.V. Artesunate and I.V. Antibiotics, developed AKI (Acute kidney injury) during the hospital stay necessitating multiple dialysis sessions before making a complete recovery. This is a rare case in several aspects as discussed below.